1972
DOI: 10.1007/bf01868051
|View full text |Cite
|
Sign up to set email alerts
|

Orientation of the porphyrin ring in artificial chlorophyll membranes

Abstract: A sensitive photometric method is described by which the dichroism of lipid bilayer membranes in aqueous phase can be measured. The method is applied to black films with incorporated chlorophylla andb. With chlorophylla a relatively large dichroism is found in the Soret band and a much weaker dichroism in the red band. From the experimental data, the angles β B and β R between the "blue" and "red" transition moments and the membrane can be obtained. β B and β R are then used to calculate the angle γ of the por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

1973
1973
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(9 citation statements)
references
References 23 publications
0
8
1
Order By: Relevance
“…An exception is the work of Yguerabide and Stryer (1971), who showed that fluorescence spectroscopy of macroscopic bilayer vesicles (1-4 mm diameter) was possible. Other spectroscopic studies have been done in special cases where chromophores (e.g., chlorophyll) are in' corporated in the BLM (black lipid membrane) (e.g., Cherry, Hsu & Chapman, 1972;Steinemann, Stark & L~iuger, 1972). For the most part, however, indirect methods must be used.…”
Section: Discussionmentioning
confidence: 98%
“…An exception is the work of Yguerabide and Stryer (1971), who showed that fluorescence spectroscopy of macroscopic bilayer vesicles (1-4 mm diameter) was possible. Other spectroscopic studies have been done in special cases where chromophores (e.g., chlorophyll) are in' corporated in the BLM (black lipid membrane) (e.g., Cherry, Hsu & Chapman, 1972;Steinemann, Stark & L~iuger, 1972). For the most part, however, indirect methods must be used.…”
Section: Discussionmentioning
confidence: 98%
“…l,,,, I,,, being direction cosines relating the direction of the molecular axis i j with the laboratory axis of rotation, and the angled brackets denote averages over all molecules in the light path. However, since the orientation of the pigment is due to the incorporation of the phytyl chain into the GMO lamellae (see Discussion, and also Steinemann et al, 1972), in the molecule-fixed coordinate system chosen above the orientation parameter matrix is diagonal:…”
Section: Treatment Of Datamentioning
confidence: 99%
“…Therefore, at small light intensities (outside the saturation region) the photocurrent should be proportional to cos 2 ~p. Assuming that the purple-membrane sheets have no preferential orientation within the plane of the bilayer, the calculation of cos 2 ~ leads to the following expression for the photocurrent I (Steinemann et al, 1972): …”
Section: Polarization Effectsmentioning
confidence: 99%